Characterization and Functional Analysis of Calmodulin and Calmodulin-Like Genes in Fragaria vesca - Zhang, Kai; Yue, Dingyi; Wei, Wei; Hu, Yang; Feng, Jiayue; Zou, Zhirong (Frontiers in Plant Science, 2016)
Calcium is a universal messenger that is involved in the modulation of diverse developmental and adaptive processes in response to various stimuli. Calmodulin (CaM) and calmodulin-like (CML) proteins are major calcium sensors in all eukaryotes, and they have been extensively investigated for many years in plants and animals. However, little is known about CaMs and CMLs in woodland strawberry (Fragaria vesca). In this study, we performed a genome-wide analysis of the strawberry genome and identified 4 CaM and 36 CML genes. Bioinformatics analyses, including gene structure, phylogenetic tree, synteny and three-dimensional model assessments, revealed the conservation and divergence of FvCaMs and FvCMLs, thus providing insight regarding their functions. In addition, the transcript abundance of four FvCaM genes and the four most related FvCML genes were examined in different tissues and in response to multiple stress and hormone treatments. Moreover, we investigated the subcellular localization of several FvCaMs and FvCMLs, revealing their potential interactions based on the localizations and potential functions. Furthermore, overexpression of five FvCaM and FvCML genes could not induce a hypersensitive response, but four of the five genes could increase resistance to Agrobacterium tumefaciens in Nicotiana benthamiana leaves. This study provides evidence for the biological roles of FvCaM and CML genes, and the results lay the foundation for future functional studies of these genes.